Comparison of polymerase chain reaction and conventional methods in detecting methicillin-resistant Staphylococcus aureus - Riza Adaleti,1 Yasar Nakipoglu,2 Zeynep Ceren Karahan,3 Cihan Tasdemir,1 Fatma Kaya.1 (The Journal of Infection in Developing Countries, 2008)
Background: Accurate and rapid detection of methicillin-resistant Staphylococcus aureus is very important in a clinical laboratory setting to avoid treatment failure. Conventional methods were compared against the gold standard polymerase chain reaction (PCR) technique to determine the best combination of the routine procedures.Methodology: Methicillin resistance was investigated in 416 clinical Staphylococcus aureus isolates by PCR, oxacillin agar screening (OAS), oxacillin disk diffusion (ODD) and cefoxitin disk diffusion (CDD) methods.Results: Two hundred and ten (51%) out of 416 S. aureus strains were found to be mecA-positive by PCR. Sensitivity and specificity of the ODD, CDD and OAS methods were detected as follows: 100% and 89%, 99.50% and 100%, and 99.50% and 100%, respectively.Conclusion: Combining the ODD and CDD methods could be a good choice for detecting methicillin resistance in S. aureus strains where mecA PCR cannot be performed.